(3ebGdI aj MjdI GdHQAs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s ((3Ydi Hf EHQGgje Hf CMeO CMeO GdJLjHi s)
(3ChdgG (B:s
(3GdZQV ef gPG Gdbhd Cf fHjf GdWQjbI GdUfGYjI ai MjdI GdHQA eGgi hdeG cGf LeghQ GdCWHGA efge QCjJ Cf CPcQgG ChdkG hCPcQ CfgG djSJ GdWQjbI GdUfGYjI s
(3BNQgG (B:s
(3hPdc eG bUOfG Edjg , hGdMeO ddg Mb MeOg cedJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3GfXQgG eY JdNjU cJGH GdMejGJ Qbe (B" 423"s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGHd GdKGfi (B- (3U (B247 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs